DWT based transformed domain feature extraction approach for epileptic seizure detection - Mostafa, Mahajabin; Samin, Mohtasim Abrar; Hassan, Nabila Bintey; Nibras, Saiara Zerin; Rahman, Samir (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.